High temperature‐insensitive ferro‐/piezoelectric properties and nanodomain structures of Pb(In1/2Nb1/2)O3–PbZrO3–Pb(Mg1/3Nb2/3)O3–PbTiO3 relaxor single crystals. Issue 3 (26th October 2017) - He, Wenhui; Li, Qiang; Xi, Xiaoqing; Yan, Qingfeng
Abstract: For rhombohedral (R) Pb(In1/2 Nb1/2 )O3 –PbZrO3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (PIN–PZ–PMN–PT) relaxor single crystal, high temperature‐insensitive behaviors under different external stimuli were observed (remnant polarization P r from 30°C to 180°C and piezoelectric strain d 33 * from 30°C to 116°C). When electric field E ≥ 50 kV/cm in the case of an activation field E a = 40‐50 kV/cm was applied, it was found that the domain switching was accompanied by a phase transition. The high relaxor nature of the R phase PIN–PZ–PMN–PT was speculated to account for the large E a and high piezoelectric response. The short‐range correlation lengths ξ extracted from the out‐of‐plane (OP) and in‐plane (IP) nanodomain images, were 64 nm and 89 nm, respectively, which proved the high relaxor nature due to In 3+ and Zr 4+ ions entering the B‐site in the ABO3 ‐lattice and enhancing the disorder of B‐site cations in the R phase PIN–PZ–PMN–PT. The switching process of R nanodomain variants under the step‐increased tip DC voltage was visually revealed. Moreover, the time‐dependent domain evolution confirmed the high relaxor nature of the R phase PIN–PZ–PMN–PT single crystal.